Conceptualizing Employee Silence and Employee Voice as Multidimensional Constructs* - Dyne, Linn Van; Ang, Soon; Botero, Isabel C. (Journal of Management Studies, 2003)
ABSTRACT Employees often have ideas, information, and opinions for constructive ways to improve work and work organizations. Sometimes these employees exercise voice and express their ideas, information, and opinions; and other times they engage in silence and withhold their ideas, information, and opinions. On the surface, expressing and withholding behaviours might appear to be polar opposites because silence implies not speaking while voice implies speaking up on important issues and problems in organizations. Challenging this simplistic notion, this paper presents a conceptual framework suggesting that employee silence and voice are best conceptualized as separate, multidimensional constructs. Based on employee motives, we differentiate three types of silence (Acquiescent Silence, Defensive Silence, and ProSocial Silence) and three parallel types of voice (Acquiescent Voice, Defensive Voice, and ProSocial Voice) where withholding important information is not simply the absence of voice. Building on this conceptual framework, we further propose that silence and voice have differential consequences to employees in work organizations. Based on fundamental differences in the overt behavioural cues provided by silence and voice, we present a series of propositions predicting that silence is more ambiguous than voice, observers are more likely to misattribute employee motives for silence than for voice, and misattributions for motives behind silence will lead to more incongruent consequences (both positive and negative) for employees (than for voice). We conclude by discussing implications for future research and for managers.